THE DETERMINATION OF THE PRIORITY OF PRONA LOCATION USING RANK SUM METHOD (A Case Study Of Purwanegara Subdistrict, Banjarnegara Regency, Central Java Province) - SETYAWAN (NIM 25106310), NANANG
The determination of PRONA location is one of important factors in the provision of land registering acceleration program. This activity is directed to improve people's economic level through land certification. So, a method which can represent quantitavely potential area to determine PRONA location priority is needed to improve the standard of community's living. The method used to determine location to be more objective is a rank sum method with equal interval classification. The data from each criteria be normalized and classified into 5 class interval in the same range, than it is arranged in a rank and its weighting use inverse ranking in accordance with its weightiness. Furthermore, each data multiplied with the initial weight from each class interval, so the result is final weight. The final score will be obtained from the result of mathematical equation as a multiplication between criteria weight from the result of quesioner with final weight. The greatest quantities will be the first priority. The selected criteria include population density, poverty level, distance of village office to land office, ratio of certified lot area to regional area, educational level, area of land use type and population work type. Analysis have done to the data and its processing, while its criteria weighting used normalization process, count analysis of PRONA location score using statistical test and analysis of its quota to PRONA certification based on technical regulation of PRONA. Based on the result of analysis, significantly influential criteria to the determination of location priority of PRONA are poverty level, ratio of certified lot area to regional area, educational level, population work type, area of land-use type, population density and distance of village office to land office. The priority of location of PRONA respectively are Purwanegara, Danaraja, Kalipelus, Gumiwang, Kalitengah, Merden, Mertasari, Karanganyar, Petir, Kaliajir, Pucungbedug, Parakan dan Kutawuluh.